2021
DOI: 10.3390/ijerph18157958
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Determinants of Nonadherence to Depression and Anxiety Medication among Individuals Experiencing Homelessness

Abstract: Psychiatric medication nonadherence continues to be a leading cause of poor health outcomes for individuals experiencing homelessness. Identifying the sociodemographic factors that contribute to medication nonadherence may help guide strategies to care for and support this group. This study examined 200 adults with depression diagnoses and active anti-depressant prescriptions (Mage = 43.98 ± 12.08, 59.4% Caucasian, 58.5% male, 70% uninsured, 89.5% unemployed) and 181 adults with anxiety diagnoses and active an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…PEH have increased rates of behaviors known to increase hypertension risk, including higher smoking rates, poor diet, and high levels of sodium in average daily nutritional intake 35–38 . Studies on health care use in PEH populations have reported cost to be a significant barrier to medication access, likely impacting adherence to antihypertensives 35–40 . PEH also navigate an environment that poses logistical and practical barriers to lifestyle changes necessary for blood pressure control and maintenance, including barriers to obtaining fresh produce and reduced access to blood pressure monitoring equipment 34,35,37–39,41 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PEH have increased rates of behaviors known to increase hypertension risk, including higher smoking rates, poor diet, and high levels of sodium in average daily nutritional intake 35–38 . Studies on health care use in PEH populations have reported cost to be a significant barrier to medication access, likely impacting adherence to antihypertensives 35–40 . PEH also navigate an environment that poses logistical and practical barriers to lifestyle changes necessary for blood pressure control and maintenance, including barriers to obtaining fresh produce and reduced access to blood pressure monitoring equipment 34,35,37–39,41 .…”
Section: Discussionmentioning
confidence: 99%
“…and Crimmins et al. have called into question the age at which older adult care should begin for low SES and housing‐insecure patients, and recommend defining older adults in at‐risk populations earlier in the life course to better match onset of age‐associated diseases 32–44 . Doing so would have clinical relevance for primary care physicians who are tasked to manage chronic diseases, such as hypertension, in vulnerable patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The health impacts of homelessness presented by Eshtehardi [ 5 ] examine prescription management in supporting a comorbid diagnosis of depression, Carroll [ 6 ] reports an absence of access to rehabilitation services, Vallesi [ 7 ] identifies tri- and multi-morbidity, identifying the pervasiveness of preventable health conditions that exist for this population and limited access to screening programmes, and Salem [ 8 ] examines the increased risk of latent tuberculosis infection. Broderick [ 9 ] presents the outcomes of a review of physical health screening tests and confirms the challenge in using unsuitable standard tests which add to increased pain and discomfort.…”
mentioning
confidence: 99%